PENDAMPINGAN UMKM BERBASIS SCORE ILO DI BOOTH MINUMAN BBY_NA JELLY COOL BENGKAYANG KALIMANTAN BARAT - Hilarianty, Hilarianty; Maisela, Maisela; Salfarini, Eligia Monixa (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The aim of MSME Assistance is an important effort to support the development of Micro, Small and Medium Enterprises (MSMEs). One of the approaches used is ILO SCORE-based, which emphasizes improving the quality and productivity of MSMEs. This study aims to evaluate the implementation of ILO SCORE-based MSME assistance at the Bby_na jelly cool drink booth in Bengkayang, West Kalimantan. This study aims to evaluate the implementation of ILO SCORE-based MSME assistance at the Bby_na jelly cool drink booth in Bengkayang, West Kalimantan. The research method used is a case lean method with the 5S concept. The research results show that ILO SCORE-based MSME assistance is able to provide significant benefits in improving product quality, marketing and management of MSMEs. The implication of this research is the importance of implementing ILO SCORE-based MSME assistance in supporting the growth and sustainability of MSMEs in Bengkayang, West Kalimantan.